Influence of secondary hyperparathyroidism in management of anemia in patients on regular hemodialysis - Hamzagić, Nedim; Andjelković, Marija; Stanojević Pirković, Marijana; Čanović, Petar; Ignjatović, Vesna; Ramović, Amra; Petrović, Dejan (Vojnosanitetski pregled, 2021)
Background/Aim. Anemia is a common complication in hemodialysis patients. Treatment of anemia is affected by iron deficiency, insufficient dose of erythropoietin, microinflammation, vitamin D deficiency, increased intact para-thyroid hormone concentration and inadequate hemodialysis. The aim of the study was to determine the prevalence of vitamin D deficiency and its impact on hemoglobin con-cen-tration, iron status, microinflammation, malnutrition, dialysis adequacy and erythropoietin dose in patients on regular hemodialysis. Methods. The study involved 120 patients divided into three groups: severely deficient of vitamin D: 25-hydroxyvitamin D [25(OH)D] < 10 ng/mL; deficient – 25(OH)D within range of 10–20 ng/mL, and insufficient – 25(OH)D > 20 ng/mL. For statistical analysis Kolmogorov-Smirnov test, the single-factor parametric analysis of variance – ANOVA and Kruskal-Wallis test were used. Results. The prevalence of vitamin D deficiency in patients on regular hemodialysis was 75.83%, while the prevalence of severe vitamin D deficiency was 24.7%. Patients with severe vitamin D deficiency had lower blood concentration of hemoglobin, hematocrit, serum concentration of total proteins and albu-min, and dialysis indices were also lower compared to the other two groups of patients. The level of C-reactive protein was significantly higher in the group of patients with severe vitamin D deficiency than in the two rest groups. Conclusion. Hemodialysis patients with severe vitamin D deficiency have lower hemoglobin, lower dialysis adequacy, significant microinflammation, malnutrition, bone meta-bo-lism disorders and need higher dose of erythropoietin than patients whose vitamin D was higher than 10 ng/mL. Vitamin D is important risk factor for development of anemia in hemodialysis patients and important factor that can affect treatment of anemia in these patients.
Keywords: anemia; erythropoietin; renal dialysis; risk factors; vitamin d